Integrating Qur’anic Values into Algebra Learning: A Pedagogical Model for Developing Islamic Scientific Character - Muhammad Rizki Ramadhan; Prima Cristi Crismono; Fitriyatul Hanifiyah; Mahnawawe Yakoh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the implementation and theoretical contribution of an integrated knowledge model that incorporates Qur’anic values into algebra instruction in order to cultivate an Islamic scientific character. The study contributes to the discourse on knowledge integration in Islamic pedagogy by proposing a contextual, mathematics-based learning model. It employs a qualitative approach with an interpretative case study design. Data were collected through classroom observations, semi-structured interviews with teachers and students, and analysis of instructional documents, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that integrating Qur’anic values into algebra instruction can be empirically implemented through structured planning, execution, and evaluation. This integration provides evidence of strengthening students’ Islamic scientific character, as reflected in increased curiosity, academic honesty, discipline, orderly thinking, and spiritual awareness. These findings expand the framework of knowledge integration by demonstrating that mathematics, particularly algebra, can serve as an effective epistemological medium for internalizing Islamic values simultaneously with cognitive development.